The implementation of augmented reality of promotional media in daihatsu dealers - Tri Handayani; Rihayes; Tri Yuliati; Ari Sellyana (Jurnal Mantik, 2023)
Some companies make product offers or promotions that aim to improve the quality and attractiveness of their products and increase consumer attractiveness. Daihatsu Duri car dealership is one of them. Augmented reality (AR) is one of the media used for product marketing. This research is how to use Augmented Reality to promote Daihatsu dealers and display 3D objects of Rocky Daihatsu cars on mobile markers as promotional media. The results of this study indicate that in the menu display experiment, one menu that was not displayed successfully was to select zoom. Testing on markers can be tested properly. For remote experiments, at a distance of 60 cm it can be detected, but not consistently. Meanwhile, light testing shows that the ambient light type of ARCamera Light is a bit dark, and markers are not detected properly. A stable internet connection is required to use this app, and lighting is also very important as AR cameras cannot detect markers in low light, so they cannot display 3D objects automatically.%MCEPASTEBIN%